PENGARUH KECERDASAN EMOSI DAN MOTIVASI BERPRESTASI TERHADAP PRESTASI BELAJAR MAHASISWA AKPARNAS-UNAS - Tine Yuliantini (Universitas Nasional, 2016)
The research aims to analyze the influence of emotional intelligence and achievement motivation to achievement in learning of students in Akparnas–Universitas Nasional Jakarta. The Research is descriptive research with used regression analusis and correlation with data os questionnaire collected from the all students at Akparnas – Universitas Nasional Jakarta. The result of research showed that Emotional Intelligence and achievement motivation have a positive and significant effect to achievement in learning. The variable achievement motivation is the most dominant variable to influence achievement in learning with almost powerful dimension is the dimension of need of achievement.